2007
DOI: 10.1590/s1020-49892007000700006
|View full text |Cite
|
Sign up to set email alerts
|

Retail prices of essential drugs in Brazil: an international comparison

Abstract: Average retail prices of essential drugs in Brazil are significantly higher than in Sweden. Furthermore, international bulk prices indicate that drugs are brought to market by Brazil's private pharmacies at prices that may be excessively high in relation to production costs, creating high profit margins. The expected price-lowering effects of competition were not identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 2 publications
0
20
0
8
Order By: Relevance
“…A study performed in Ghana found that 93% of patients did not comply with their antihypertensive treatment regimen, 96% of which reported high medicine prices as the reason for not complying [8]. Other studies investigating medicine pricing in general, including cardiovascular medicines, found that medicines were generally poorly available and highly priced [9-12]. …”
Section: Introductionmentioning
confidence: 99%
“…A study performed in Ghana found that 93% of patients did not comply with their antihypertensive treatment regimen, 96% of which reported high medicine prices as the reason for not complying [8]. Other studies investigating medicine pricing in general, including cardiovascular medicines, found that medicines were generally poorly available and highly priced [9-12]. …”
Section: Introductionmentioning
confidence: 99%
“…O caso em estudo reforça, portanto, a tese de que o sistema de concessão de patentes atual, particularmente na área da inovação farmacêutica, está fora de equilíbrio, fornecendo recompensas financeiras excessivas aos detentores patentários, sobretudo das grandes empresas farmacêuticas. No Brasil, essa situação parece ser amplificada, com o preço médio de medicamentos sendo 1,9 vez o praticado na Suécia e 13,1 vezes o índice mundial 29 .…”
Section: Discussionunclassified
“…Almost after four decades, the first Brazilian EML was formulated; many research reported that EMs were moderately available in Brazilian public health facilities. [ 85 86 87 88 ] The up-to-date seventh edited version that was released in 2010 has more and more been included medicines and its formulations for pediatric use. [ 89 90 ] It has been reported that in general, the accessibility of EMs in the public health centers was 68.8%–81.7%.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%